The Use of Arteriovenous Fistulae as an Adjunct to Peripheral Arterial Bypass: A Systematic Review and Meta-analysis. Issue 5 (May 2016) - Aherne, T.; Kheirelseid, E.; O'Neill, D.; Bashar, K.; Cullen, P.; Whitford, D.; Naughton, P.
Abstract : Background: Peripheral arterial bypass is an effective procedure for the management of patients with critical limb ischaemia. However, it is commonly associated with high rates of graft occlusion and subsequent limb loss. This is particularly apparent when the distal anastomosis is to the below-knee arterial segment. A number of studies have suggested that an arteriovenous fistula (AVF) sited at the distal anastomosis may reduce afterload, improve graft patency, and boost subsequent limb salvage. The aim of this study was to assess the effects of adjuvant AVF on the outcomes of peripheral arterial bypass. Methods: The following databases were searched up to May 2015: Medline through Pubmed; the Cochrane Library; EMBASE; and reference lists of articles. Study eligibility: All randomised controlled and observational studies that assessed the role of AVF as an adjunct to peripheral arterial bypass were included. Studies were required to include at least one pre-defined outcome. Data were extracted and assessed by two reviewers with any disagreements adjudicated on by the senior author. Pooled risk ratios were calculated using a random effects model. Additional subgroup analyses were performed. Results: Two randomised controlled trials and seven retrospective cohort studies comprising 966 participants were included. Pooled standardized data showed no difference in primary graft patency (pooled RR = 1.25, 95% CI 0.73–2.16), secondary patency (pooled RR = 1.16, 95% CI 0.82–1.66), or limb salvage at 12-months (pooled RR = 1.13, 95% CI 0.80–1.60) for the peripheral bypass with AVF group compared with peripheral bypass alone. Subgroup analysis indicated a reduction in reintervention rates associated with AVF when performed in conjunction with a synthetic graft (pooled RR = 0.55, 95% CI 0.30–0.98). Conclusion: Although adjuvant AVF is not associated with additional operative complication there is little evidence to support its use. The evidence assessing its merits is weakened by small, retrospective studies with heterogeneous cohorts.